Czy możliwa jest etyka naukowa? Wczesna twórczość etyczna Tadeusza Stycznia SDS - WIŚNIEWSKI, Ryszard (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
The article is focused on the early, so far unpublished ethical output of Tadeusz Styczeń, which includes his Master’s thesis on Nicolai Hartmann’s virtue ethics and his doctoral dissertation, in which he critically explored John Locke’s concept of moral science. In the first of these works, Styczeń, drawing on the original texts, arrives at the conclusion that Hartmann’s declared intention of a synthesis of modern phenomenological ethics and classical ethics was unsuccessful, at least in the field of virtue ethics, due to the fact that he deprived ethics and its Aristotelian tradition of the qualities of: realism, teleological unity of being and value, and rationality of moral knowledge. While highly evaluating the cognitive value of this work, as well as appreciat− ing its pioneering character on the Polish ground, the author of the article points that in the light of the newest research of the foundations of virtue ethics in Aristotle, some reservations Styczeń makes might turn out arguable. In the second work analyzed in the article, Styczeń attempts an application of Locke’s theory of science (epistemology and methodology) to the empirical, real world of morality. This procedure demonstrates Locke’s significant failure which results from his obscure use of the concepts of reality and experience on the grounds of ethics. However, the course of the critical analyses advanced by Styczeń simultaneously reveals the complex nature of the problem of the synthesis of the imperative aspect of ethics and its realistic attitude to moral experience. The author of the article is convinced that the path Styczeń started to follow in his doctoral dissertation turned out crucial in shaping his further metaethical and ethical research, which culminated in his post−doctoral dissertation, and which touches the key problems of modern ethics. Translated by Dorota Chabrajska